CONDITION OPTIMIZATION PRODUCTION XYLANASE THERMOSTABLE BY Bacillus licheniformis TS10 USING SUBSTRATE OIL PALM EMPTY FRUIT BUNCHES - Safitri, Ayu; Muharni, -; Kusumawati, Heni Yohandini (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
Optimization conditions for thermostable xylanase production of Bacillus licheniformis TS10 by using substrate oil palm empty fruit bunches has been conducted from November 2015 to January 2016 in the Laboratory of Genetics and Biotechnology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Sriwijaya, Indralaya. The aims of this study was to determine the potential of oil palm empty fruit bunches ( EFB ) as a substrate for the production of thermostable xylanase by Bacillus licheniformis TS10 and the optimum conditions of temperature, pH and substrate concentration in the fermentation process. The research method is to make the growth curve and the curve of Bacillus licheniformis TS10 enzyme production on EFB substrate. The number of bacterial cells was determined by using a UV-VIS spectrophotometer and total plate count (TPC) through a standard curve. Optimization performed at various pH (5, 6, 7, 8, 9), temperature (50 °C, 60 °C, 70 °C, 80 °C) and substrate (1%, 2%, 3%, 4%) , Test activity at each pH, temperature and substrate using methods DNS by measuring enzyme activity based on the reducing sugar released by the substrate by using dinitrosalicylic acid (DNS). Based on the results of this research showed that oil palm empty fruit bunches (EFB ) has potential as a substrate for the production of thermostable xylanase by Bacillus licheniformis TS10, thermostable xylanase production of Bacillus licheniformis TS10 on the substrate EFB has an optimum condition at pH 6, 80 °C and the substrate concentration of 4%.